English Summative Test: The Quality of Its Items - Semiun, Thresia Trivict; Wisrance, Maria Wihelmina; Napitupulu, Merlin Helentina (Universitas Nusantara PGRI Kediri, 2022)
It is crucial to implement evaluation after the teaching and learning process. Evaluation will reflect the success of teaching and more important the achievement of the students. Therefore, EFL teachers should develop a good test to measure students' achievement. This study analyzed multiple-choice items of English summative tests constructed by junior high school EFL teachers in Kupang, NTT. The result of this analysis functions as feedback to the English teachers on the quality of English summative tests they had created. This research was descriptive research with documentation for data collection.The English summative tests for grades VIII and IX were collected and then analyzed by using ITEMAN software to reveal item difficulty, item discrimination, and distracters effectiveness of the tests. The findings revealed that the English summative tests were developed with easy items. However, the tests still had a good discriminatory level. The test items which had all distracters perform well were only half of the total items.